Pengaruh Steroid Anabolik Methandienone terhadap Kualitas Spermatozoa Tikus Putih (Rattus norvegicus) - Nurul Marfu'ah (Pharmasipha : Pharmaceutical Journal of Islamic Pharmacy, 2017)
Anabolic steroids are chemical derivative of the testosterone hormone that are commonly used in medical field, but in development it is abused by its users. Methandienone is one type of anabolic steroid that widely used in the world. The anabolic effects can develop muscle formation, but the androgenic effect can suppress testosterone synthesis. Low testosterone will disrupt spermatogenesis and ultimately decrease the quality of spermatozoa production. This study aim to determine effect of anabolic steroid methandienone to quality of spermatozoa in albino rats (Rattus norvegicus). Examination of the quality of spermatozoa was performed on cauda epididymal include speed, motility, viability, and morphology of spermatozoa. The results of this study showed that the average quality of spermatozoa between the control group and the treatment group statistically was not significantly different (P > 0.05). However, average quality of spermatozoa (speed of spermatozoa, percentage of motile spermatozoa, percentage of alive spermatozoa, percentage of normal spermatozoa) also showed a declining trend. Speed of spermatozoa was normal because it is able to move in 1-4 mm/min. Motility and morphology of spermatozoa was normal because the percentage of motile spermatozoa and normal spermatozoa showed more than 50%. Viability of spermatozoa in the treatment group was abnormal because the percentage of alive spermatozoa showed less than 25%.